Abiotic stress triggers ROS-mediated programmed cell death in banana (Musa sp., AAA group, Cavendish sub-group) fruit - Ramírez Sánchez, Maricruz (2021)
Degradative processes of fleshy fruit adapt depending on environmental conditions. Exposure of banana fruit to abiotic stress during ripening accelerates degradative processes that resemble Programmed Cell Death (PCD). This research evaluated the connection between Reactive Oxygen Species (ROS) production and PCD processes during ripening and over-ripening of banana fruit after exposure to abiotic stress at the pre-climacteric phase (before exogenous ethylene treatment). Mature-green banana exposed to 1 °C for 7 d exhibited severe chilling damage. During ripening and over-ripening, epidermis cells in chilled peel developed evident browning since 2 d compared to non-chilled peel, as well as loss of cell structure and accelerated collapse. During the evaluation period H2O2 production was higher in chilled peel (˃31% of maximum) than in non-chilled (<26% of maximum) whereas production of O2•− and •OH equally increased in both chilled and non-chilled tissue until 10 d, •OH production was higher (100% of maximum) on chilled tissue by the end of overripening. Nuclease activity increased in non-chilled tissue since 0 d reaching values of 255.9 units kg−1 fresh weight s−1 at 12 d, while on chilled tissue increased since 2 d from 0 to 212.9 units kg−1 fresh weight s−1. Similarly, protease activity increased on chilled tissue after 2 d, ranging from 1800 to 152,814 units kg−1 protein s−1. However, the levels of DNA degradation or tailing were evident on non-chilled peel since 6 d, once fruit was yellow, while remained low on chilled tissue, never reaching the degradation levels of non-chilled tissue. Our results demonstrated an evident alteration in metabolism due to dehydration, enzymatic and oxidative damage. Therefore, banana fruit exposed to abiotic stress during the pre-climacteric phase developed an accelerated loss in the capacity to maintain redox homeostasis, and the banana peel showed a necrotic form of ROS-mediated PCD.